2003
DOI: 10.1016/s0954-6111(03)00124-0
|View full text |Cite
|
Sign up to set email alerts
|

KL-6, a human MUC1 mucin, is expressed early in premature lung

Abstract: KL-6, one of the MUC1 antigens, is a mucin-like high-molecular-weight glycoprotein, which is strongly expressed on type II pneumocytes. Serum levels of KL-6 have been shown to correlate with activity of interstitial pneumonia (IP). During embryonic development, MUC1 expression coincides with the onset of epithelial sheet and glandular formation. To investigate the potential role of KL-6 in lung morphogenesis, we examined KL-6 expression by immunohistochemistry on autopsied lung tissue specimens of 35 neonates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…KL-6, a mucin-like high-molecular-weight glycoprotein, has been shown to correlate with activity of interstitial pneumonia [14]. Previous studies showed higher bronchial reactivity and anomalous pulmonary venous return in TS patients [15, 16], but there are no reports showing an association between TS and interstitial lung diseases or KL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KL-6, a mucin-like high-molecular-weight glycoprotein, has been shown to correlate with activity of interstitial pneumonia [14]. Previous studies showed higher bronchial reactivity and anomalous pulmonary venous return in TS patients [15, 16], but there are no reports showing an association between TS and interstitial lung diseases or KL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed higher bronchial reactivity and anomalous pulmonary venous return in TS patients [15, 16], but there are no reports showing an association between TS and interstitial lung diseases or KL-6. Sun et al [14] reported that KL-6 was expressed in the lungs of premature neonates and infants with gestational age from 23 to 40 weeks. The sustained high level of KL-6 in the present case may be related to a possible prematurity of the lungs in TS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous immunohistochemical study revealed that type II cells obtained from premature lungs expressed KL-6 as early as 23 wk GA (16). We previously found an increase of the plasma KL-6 level in infants with BPD, suggesting that KL-6 was an early marker of BPD and an indicator of its severity (17).…”
mentioning
confidence: 84%
“…20–22 Moreover, a possible role of MUC1 in cellular adhesion mechanisms during organogenesis has been proposed. 21 Taking into account these reports and also the adherent and anti-adherent properties of Muc1/MUC1 as well as its relationship with signal transduction, it would be expected that Muc1 appears early in epithelial development in mammalian species.…”
Section: Introductionmentioning
confidence: 99%